Analysis on the Impact of Renewable Energy to Power System Fault Level - A. Z. Adnan; M. E. Yusoff; H. Hashim (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Distributed Generation is generation of electricity from renewable energy resources, located closer to the customers or loads. Installation of Distributed Generation could improve voltage and power quality, mitigate voltage sags, minimize transmission system congestion, and provide more affordable capacity for utilizing renewable energy resources. However, high penetration of Distributed Generation to the existing national grid system may contribute several impacts including fault level, as well as the performance of power system protection. Monitoring of fault level is important in power system protection in order to sustain the health of power system networks. This paper investigates the impact of installing Distributed Generation to power system fault level. Three-phase symmetrical fault is simulated and analyzed for various sizes of distributed generation in IEEE 30 bus system using Power System Simulation for Engineering (PSS/E) software.Distributed Generation is generation of electricity from renewable energy resources, located closer to the customers or loads. Installation of Distributed Generation could improve voltage and power quality, mitigate voltage sags, minimize transmission system congestion, and provide more affordable capacity for utilizing renewable energy resources. However, high penetration of Distributed Generation to the existing national grid system may contribute several impacts including fault level, as well as the performance of power system protection. Monitoring of fault level is important in power system protection in order to sustain the health of power system networks. This paper investigates the impact of installing Distributed Generation to power system fault level. Three-phase symmetrical fault is simulated and analyzed for various sizes of distributed generation in IEEE 30 bus system using Power System Simulation for Engineering (PSS/E) software.